Inclusion of carbohydrate antigen 242 in addition to carbohydrate antigen 19.9 in serological workup of carcinoma gall bladder: a case series analysis - Misra, Mragank; Mishra, Medha; Agarwal, Preeti; Gupta, Sameer; Anand, Akshay; Ali, Wahid; Maurya, Malti K.; Singh, Ajay K. (International Journal of Research in Medical Sciences, 2023)
Background: Common antigenic pool is seen because of shared embryonic origins of gall bladder cancer (GBC) and pancreas. Hence, we analyzed the role of serum carbohydrate antigen 242 (CA242) which has been studied in pancreatic cancer, in GBC. The objectives were to identify whether serum CA242 provides added advantage in diagnosis of GBC when compared to controls and to determine its cut-off value. Methods: Serum CA 19-9 level was determined by chemiluminescent micro particle assay and CA242 by enzyme linked immunosorbent assay (ELISA) of age matched cases and controls. Results: Total enrolled patients were 83 including 10 (11.7%) healthy volunteers, 22 (25.9%) chronic cholecystitis cases, and 53 (62.4%) patients with histological evidence of carcinoma. Mean age of presentation of GBC was 51.64 SD10.88 years with F: M ratio of 5.6:1. Pain (90.6%, 48/53) accompanied with jaundice was significantly associated with GBC well reflected by significantly raised serum total bilirubin (p=0.011), direct bilirubin (p=0.008) along with alkaline phosphatase levels (p=0.001). Significantly higher median value of CA 19-9 and CA242 was observed in GBC when compared to CC and healthy volunteers (p<0.001) with a significant correlation between tumor size (>2.5 cm) and serum levels of CA242. The best cut-off limit for CA242 was 45.25 IU/ml. The specificity for carcinoma diagnosis increased to 100% when CA242 was included along with CA 19.9 in serological estimation. Conclusions: We recommend that CA antigen 19-9 may be complimented with CA242 for serological identification of malignancy in the gall bladder.